Carbon dot-loaded and controllable release composite hydrogel and application thereof

CN121891294BActive Publication Date: 2026-10-30NORTHWEST UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610135120.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-01-30
Publication Date
2026-10-30
Estimated Expiration
2046-01-30

AI Technical Summary

Technical Problem

[0004]术后感染是骨修复领域常见的严重并发症,然而感染性骨微环境复杂,不仅存在细菌侵袭,还常伴随过度的炎症反应,后者会显著抑制骨再生过程

Benefits of technology

1、本发明提供了一种负载碳点并可控释放的复合水凝胶,该复合水凝胶由水凝胶基质和碳点控制单元构成,碳点控制单元封装于水凝胶基质中;碳点控制单元为CAC4A·His CDs复合物,其是将His通过水热合成法制备成His CDs,随后通过主客体相互作用的方式,将组氨酸碳量子点负载于缺氧响应性大环分子容器-羧化偶氮杯[4]芳烃中,构建缺氧响应性复合物;水凝胶基质为甲基丙烯酰化明胶和甲基丙烯酰化岩藻多糖。将具有缺氧响应特性的碳点控制单元均匀分散于水凝胶基材预聚液中并交联固化,获得该复合水凝胶。该复合水凝胶在缺氧微环境中能够特异性响应并释放His CDs,从而表现出显著的抗菌、抗炎及促进成骨分化的多重生物学功效。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121891294B_ABST
    Figure CN121891294B_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of infectious bone defect repair, and specifically relates to a composite hydrogel loaded with carbon dots and capable of controlled release and a preparation method and application thereof. The present application first prepares histidine carbon quantum dots through a hydrothermal synthesis method, then loads the histidine carbon quantum dots in an oxygen response macrocyclic molecular container-carboxylated azo calix[4]arene through host-guest interaction to construct an oxygen response carbon dot control unit; the hydrogel matrix is methacrylated gelatin and methacrylated fucoidan; finally, the oxygen response carbon dot control unit is dispersed in the hydrogel matrix to obtain the composite hydrogel loaded with carbon dots and capable of controlled release. The composite hydrogel loaded with carbon dots and capable of controlled release can specifically respond to and release histidine carbon quantum dots in an oxygen-deficient microenvironment, thereby exhibiting remarkable multiple biological functions of antibiosis, anti-inflammation and promotion of osteogenic differentiation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of composite hydrogel technology, specifically a composite hydrogel loaded with carbon dots and capable of controlled release, and its applications. Background Technology

[0002] Large-area bone defects are often caused by severe trauma, bacterial infection, open fractures, and bone tumor resection, and their repair and regeneration are significant clinical challenges. Currently, autologous and allogeneic bone transplantation are the "gold standard" for treating bone defects, but these methods have significant limitations, including limited donor sources, a high risk of secondary trauma and pain, and high complications. More seriously, severe bone defects often lead to damage to the local microvascular system, resulting in insufficient tissue perfusion and a sharp decline in oxygen supply, thus creating a persistent hypoxic microenvironment. This hypoxic condition not only hinders the survival and function of osteoblasts but also exacerbates the inflammatory response, severely impeding the natural healing process of bone tissue.

[0003] Significant progress has been made in the field of biomaterials to address these challenges. Among them, hydrogels have shown great potential in bone repair applications due to their unique physicochemical properties. Ideal hydrogel materials typically possess good biocompatibility, biodegradability, and tunable physicochemical properties (such as rheological and mechanical properties). In addition, many hydrogels also have excellent injectability and in-situ molding capabilities, enabling precise filling of irregular bone defects and cavities, thus achieving minimally invasive treatment.

[0004] Postoperative infection is a common and serious complication in the field of bone repair. However, the infectious bone microenvironment is complex, not only subject to bacterial invasion but also often accompanied by excessive inflammatory responses, which can significantly inhibit the bone regeneration process. Although traditional hydrogels are widely used in bone repair, their inherent antibacterial, immunomodulatory, and osteogenic induction activities are very limited, making it difficult to address the aforementioned multiple challenges. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a composite hydrogel with controlled release of carbon dots and its applications. The invention first provides a carbon dot control unit, namely the CAC4A·His CDs complex. Further, the carbon dot control unit is encapsulated within a hydrogel matrix, which consists of methacrylamide gelatin (Gel MA) and methacrylamide fucoidan (F-MA). After encapsulation of the CAC4A·His CDs complex by F-MA and Gel MA, F-MA and Gel MA crosslink through photo-initiated free radical polymerization to form a three-dimensional network structure, thereby constructing a composite hydrogel system capable of controlled release. This composite hydrogel can intelligently respond to the hypoxic microenvironment of bone defect areas, specifically releasing histidine carbon quantum dots (His CDs), thereby exerting multiple biological effects such as highly efficient antibacterial, anti-inflammatory, and osteogenic differentiation promotion, ultimately achieving effective repair of infected bone defects. This invention integrates a functional carbon dot control unit into a hydrogel matrix to construct a multifunctional composite system, developing an intelligent composite hydrogel that integrates highly efficient antibacterial, anti-inflammatory, and osteogenic properties.

[0006] To solve the above-mentioned technical problems, the present invention adopts the following technical solution: This invention protects a composite hydrogel loaded with carbon dots and capable of controlled release, which consists of a hydrogel matrix and a carbon dot control unit. The carbon dot control unit is encapsulated in the hydrogel matrix. The carbon dot control unit is an anoxic response complex formed by carboxylated azocalixarene [4]arene (CAC4A) encapsulating His CDs through host-guest interactions, namely, the CAC4A·His CDs complex. The hydrogel matrix is ​​methacrylated gelatin (Gel MA) and methacrylated fucoidan (F-MA).

[0007] Furthermore, this invention also protects a method for preparing a composite hydrogel loaded with carbon dots and capable of controlled release, comprising the following steps: (1) The carbon dot control unit is a CAC4A·His CDs complex, and the CAC4A·His CDs complex is prepared. (2) Preparation of F-MA and Gel MA; (3) The CAC4A·His CDs complex obtained in step (1) is mixed with the F-MA and Gel MA obtained in step (2), and crosslinked by photoinitiation to obtain the final composite hydrogel with loaded carbon dots and controllable release. Furthermore, the preparation method of the CAC4A·His CDs complex in step (1) includes: 1) Preparation of His CDs: Add 0.5g~2g of histidine (His) to 10mL~20mL of deionized water and stir until completely dissolved to obtain a clear solution; transfer the clear solution to a high-pressure reactor lined with polytetrafluoroethylene and hydrothermally react at 180℃ for 6h~10h. Histidine small molecules undergo dehydration, condensation, polymerization and carbonization from bottom to top to finally form carbon quantum dots. Specifically, histidine, as a precursor, forms histidine carbon quantum dots through polymerization and carbonization; after the reaction is completed, allow it to cool naturally to room temperature, filter the resulting reaction solution to remove large particulate impurities, and then dialyze it in a dialysis bag with a molecular weight cutoff of 1000Da for 12h~24h. Finally, freeze-dry to obtain His CDs powder. 2) Preparation of CAC4A: 4-aminobenzoic acid and 1 mL to 3 mL of concentrated hydrochloric acid were dissolved together in pure water. Sodium nitrite was added dropwise under ice-water bath conditions to carry out diazotization reaction. Under hydrochloric acid conditions, sodium nitrite reacted with hydrochloric acid to generate nitrous acid. Nitrous acid reacted with 4-aminobenzoic acid molecules to obtain a diazonium salt solution. 25,26,27,28-tetrahydroxycalix[4]arene (C4A) and sodium acetate were added together to a methanol-N,N-dimethylformamide mixed solvent and stirred to dissolve to obtain a C4A solution. Under 0℃ to 5℃ and stirring conditions, the diazonium salt solution was added dropwise to the C4A solution and the reaction was continued for 2 h. An electrophilic substitution reaction was carried out. The diazonium salt attacked the para position of the phenolic hydroxyl group on the benzene ring in C4A. After the reaction was completed, the pH of the solution was adjusted with hydrochloric acid. Then the temperature was raised to 60℃ and the reaction was carried out for 30 min. After the reaction was completed, the obtained suspension was centrifuged. The precipitate was washed with water and ethanol in sequence and dried to obtain CAC4A. 3) Preparation of CAC4A·His CDs complex: His CDs and CAC4A were mixed in water, with the final concentration of His CDs being 1000 μg / mL~2000 μg / mL and the final concentration of CAC4A being 300 μg / mL~500 μg / mL. After mixing, the mixture was stirred under light-protected conditions. With CAC4A as the host and His CDs as the guest, the two were bonded by non-covalent bonds, and the CAC4A·His CDs complex was obtained through self-assembly by host-guest interaction.

[0008] Furthermore, the preparation methods of F-MA and Gel MA in step (2) include: 1) Preparation of F-MA: Fucoidan was added to deionized water, heated to 50℃ and stirred continuously to fully dissolve the fucoidan, preparing a solution with a mass fraction of 1%~3%; while stirring, 4mL~12mL of methacrylic anhydride (MA) was added dropwise to the solution, and after stirring for 1h, the pH of the system was adjusted to 8 with sodium hydroxide, and the reaction was continued for 4h, and the pH was adjusted to 8 again to ensure that the reaction was fully carried out, and the hydroxyl groups on the fucoidan chain underwent an esterification reaction with the anhydride groups of methacrylic anhydride; the reaction solution was kept at 50℃ and stirred for 6h; after the reaction was completed, the solution was cooled to room temperature, and then dialyzed with Milli-Q water for 1 week. Finally, the dialyzed solution was freeze-dried to obtain F-MA.

[0009] 2) Preparation of Gel MA: Weigh 1g of gelatin powder and add it to 10mL of PBS solution. Stir at 50℃ until completely dissolved. Add MA dropwise under continuous stirring and react in the dark for 4h. The amino group of lysine residue in gelatin molecules undergoes amidation reaction with the anhydride group of methacrylic anhydride. After the reaction is completed, dilute with 5 times the volume of PBS solution to terminate the reaction. Then place the solution in a dialysis bag with a molecular weight cutoff of 8000Da~12000Da and dialyze with Milli-Q water for 1 week. Finally, obtain Gel MA by freeze drying.

[0010] Furthermore, the preparation conditions of the composite hydrogel described in step (3) are as follows: F-MA and Gel MA were prepared into aqueous solutions with a mass-volume concentration of 2%-4% (w / v) and 5%-10% (w / v), respectively. The two solutions were mixed uniformly at a 1:1 volume ratio to obtain a hydrogel substrate prepolymer solution. A CAC4A·His CDs composite was added to the hydrogel substrate prepolymer solution to a final system concentration of 300 μg / mL to 500 μg / mL, and the mixture was stirred until uniformly dispersed. Subsequently, a photoinitiator, lithium phenyl-2,4,6-trimethylbenzoylphosphine (LAP), was added at 0.05% to 0.25% (w / w) of the total mass of the hydrogel substrate prepolymer solution, and the mixture was stirred until completely dissolved to obtain a mixed solution. At this point, F-MA and Gel MA encapsulated the CAC4A·His CDs composite solution, including loading and coating. Finally, the mixed solution was irradiated under 405 nm blue light. The carbon-carbon double bonds of MA molecules undergo homolytic cleavage under photoexcitation, generating free radicals, which in turn initiate polymerization and cross-linking to form a composite hydrogel loaded with carbon dots and capable of controlled release, namely F-MA / Gel MA CH composite hydrogel.

[0011] Preferably, the hydrothermal reaction conditions are: reaction at 180℃ for 6 to 10 hours.

[0012] Preferably, the diazotization reaction is carried out under the following conditions: stirring at 0℃~5℃ for 30 min~1 h.

[0013] Preferably, the electrophilic substitution reaction conditions are as follows: at 0℃~5℃, the reaction is stirred for 2h~3h, after the reaction is completed, the pH is adjusted to 0.9~1.2, and the reaction is continued to be stirred at 50~60℃ for 15min~45min.

[0014] Preferably, the mass ratio of 4-aminobenzoic acid to 25,26,27,28-tetrahydroxycalix[4] aromatic hydrocarbon is 1~3:0.5~2.

[0015] Preferably, during self-assembly, the stirring time in the dark is 10 min to 1 h.

[0016] Preferably, the mass ratio of His CDs to CAC4A is 10~20:3~5.

[0017] Preferably, the esterification reaction conditions are as follows: at 40~60℃, the reaction is stirred for 30min~2h, then the pH is adjusted to 8.0~9.0, and the reaction is continued to be stirred for 3~5h, and then the pH is adjusted to 8.0~9.0 again. During the reaction, the pH of the solution system will decrease, and the pH value needs to be adjusted multiple times.

[0018] Preferably, the mass ratio of fucoidan to methacrylic anhydride is 1~3:4~12.

[0019] Preferably, the conditions for the amidation reaction are: stirring at room temperature in the dark for 4 to 6 hours.

[0020] Preferably, the mass ratio of gelatin to methacrylic anhydride is 0.5~2:1~4.

[0021] Preferably, the mass-volume concentration of F-MA in the hydrogel substrate prepolymer is 2%~4%, and the mass-volume concentration of Gel MA is 5%~10%.

[0022] Preferably, the conditions for photo-initiated free radical polymerization crosslinking reaction are: irradiation with blue light at a wavelength of 405 nm for 1 min to 5 min.

[0023] This invention also protects the application of composite hydrogels loaded with carbon dots and capable of controlled release in the preparation of materials for repairing infected bone defects.

[0024] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention provides a composite hydrogel loaded with carbon dots and controllable release. The composite hydrogel consists of a hydrogel matrix and a carbon dot control unit, which is encapsulated in the hydrogel matrix. The carbon dot control unit is a CAC4A·His CDs complex, which is prepared by hydrothermal synthesis of His CDs, and then histidine carbon quantum dots are loaded into hypoxia-responsive macrocyclic molecular container - carboxylated azocalix[4] aromatic hydrocarbon through host-guest interaction to construct a hypoxia-responsive complex. The hydrogel matrix consists of methacrylamide gelatin and methacrylamide fucoidan. The carbon dot control unit with hypoxia-responsive properties is uniformly dispersed in the prepolymer of the hydrogel matrix and crosslinked and cured to obtain the composite hydrogel. The composite hydrogel can specifically respond to and release His CDs in a hypoxia-deficient microenvironment, thereby exhibiting significant antibacterial, anti-inflammatory and osteogenic differentiation-promoting multiple biological effects.

[0025] The core of the CAC4A·His CDs complex constructed in this invention lies in the self-assembly and binding between the CAC4A macrocyclic molecule and HisCDs through host-guest interactions. This binding method is mild and efficient, and maintains the functional integrity of the bioactive components to the greatest extent.

[0026] The CAC4A·His CDs complex constructed in this invention has unique hypoxia-responsive drug release characteristics. In the hypoxic microenvironment unique to infectious bone defects, the structure of CAC4A will change, thereby intelligently releasing the loaded HisCDs, realizing targeted and on-demand drug release, and synergistically exerting the dual biological effects of precise antibacterial and efficient bone differentiation promotion.

[0027] The hydrogel matrix constructed in this invention is composed of methacrylamide gelatin (Gel MA) and methacrylamide fucoidan (F-MA). This system combines Gel MA (which has good biocompatibility, controllable degradation and osteoinductive activity) with F-MA, a natural sulfated polysaccharide derived from seaweed (which has significant anti-inflammatory and immunomodulatory functions), to simulate the natural extracellular matrix microenvironment, thereby providing a biomimetic and more suitable support environment for cell attachment, proliferation and differentiation.

[0028] 2. The composite hydrogel prepared by this invention possesses excellent injectability and in-situ light-curing capability. During operation, the composite hydrogel is directly injected into irregular bone defect cavities, allowing it to fully fill and conform to the defect contour. Subsequently, it can rapidly cross-link and cure after a short period of blue light irradiation, achieving a combination of minimally invasive implantation and personalized adaptation.

[0029] 3. The preparation method provided by this invention has a clear principle, a simple preparation method, high biocompatibility of raw materials, and does not require complex and expensive equipment, thus having good prospects for promotion. Attached Figure Description

[0030] Figure 1 Transmission electron microscope (TEM) image of His CDs prepared in Example 1 of this invention.

[0031] Figure 2 This is a hypoxia-responsive release diagram of CAC4A·His CDs from Example 1.

[0032] Figure 3 The image shows the results of the in vitro antibacterial experiment of His CDs in Example 1.

[0033] Figure 4 This is a schematic diagram of the gelation process of the F-MA / Gel MA CH composite hydrogel precursor solution of Example 1 undergoing cross-linking and curing after light irradiation.

[0034] Figure 5 The image shows a scanning electron microscope (SEM) image of the F-MA / Gel MA CH composite hydrogel from Example 1.

[0035] Figure 6 The image shows the effect of alkaline phosphatase (ALP) staining on the F-MA / Gel MA CH composite hydrogel of Example 1 to evaluate its effect on inducing osteogenic differentiation of cells in vitro.

[0036] Figure 7 The image shows the bone repair effect of the F-MA / Gel MA CH composite hydrogel in an infected bone defect model, as described in Example 1. Detailed Implementation

[0037] To enable those skilled in the art to better understand and implement the technical solutions of the present invention, the present invention will be further described below with reference to specific embodiments and accompanying drawings. However, the embodiments described are not intended to limit the present invention. Unless otherwise specified, the experimental methods and detection methods described in the following embodiments are conventional methods; unless otherwise specified, the reagents and materials described are commercially available.

[0038] In the following examples, histidine, calix[4] aryl hydrocarbons, fucoidan and methacrylic anhydride were purchased from Shanghai Maclean Biochemical Technology Co., Ltd.; 4-aminobenzoic acid, sodium nitrite and sodium acetate were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; and fish skin gelatin was purchased from Shanghai Yuanye Biotechnology Co., Ltd.

[0039] Example 1 A method for preparing a composite hydrogel loaded with carbon dots and capable of controlled release includes the following steps: Preparation of CAC4A·His CDs complex: S1. Weigh 1g of histidine (His) and add it to 20mL of deionized water. Stir until completely dissolved to obtain a clear His solution with a concentration of 50mg / mL, which is used as the reaction precursor. Transfer the His clear solution to a high-pressure reactor with a polytetrafluoroethylene liner and react at 180℃ for 10h. After the reaction is completed, allow it to cool naturally to room temperature. Filter the resulting reaction solution to remove large particulate impurities, and then dialyze it in a dialysis bag with a molecular weight cutoff of 1000Da for 24h. Finally, freeze-dry to obtain histidine carbon quantum dots (His CDs) powder.

[0040] S2. Weigh 4-aminobenzoic acid (10 mmol) and dissolve it together with concentrated hydrochloric acid (2 mL) in 15 mL of deionized water. Cool it to 5 °C in an ice-water bath, and then slowly add sodium nitrite aqueous solution (10 mmol) under stirring. Stir for 30 min to obtain a diazonium salt solution. Weigh 25,26,27,28-tetrahydroxycalix[4]arene (C4A, 2.36 mmol) and sodium acetate (30 mmol), dissolve them in 26 mL of methanol-N,N-dimethylformamide mixed solvent (methanol to DMF volume ratio of 5:8), and stir until dissolved. C4A solution was obtained, and then the diazonium salt solution was slowly added dropwise to the C4A solution at 5℃ and under stirring conditions. After the addition was completed, the reaction was continued at the same temperature for 2 hours. After the reaction was completed, the pH of the solution was adjusted to 1 with hydrochloric acid, and then the temperature was raised to 60℃ and the reaction was carried out for 30 minutes. After the reaction was completed, the reaction system was cooled to room temperature, and the resulting suspension was centrifuged at 8000 rpm for 10 minutes to collect the precipitate. The precipitate was washed with deionized water and anhydrous ethanol in sequence, and finally dried in a vacuum drying oven at 40℃ to obtain the brick-red solid product carboxylated azocalix[4] aromatic hydrocarbon (CAC4A).

[0041] S3. Prepare an aqueous solution of His CDs powder with a concentration of 2000 μg / mL as His CDs stock solution. Under stirring conditions, add CAC4A solution to the His CDs stock solution to make the final concentration of His CDs in the mixture 1000 μg / mL and the final concentration of CAC4A 500 μg / mL. Then stir in the dark for 30 min and obtain the CAC4A·His CDs complex through self-assembly by host-guest interaction.

[0042] Preparation of F-MA and Gel MA: Weigh 1g of fucoidan and add it to 100mL of deionized water. Heat the solution to 50℃ and stir continuously to fully dissolve the fucoidan, preparing a solution with a concentration of 10mg / mL. While stirring, slowly add 12mL of methacrylic anhydride (MA) to the solution. Continue stirring for 1 hour, then adjust the pH of the system to 8 with sodium hydroxide. Continue the reaction for 4 hours, then adjust the pH to 8 again to ensure the reaction proceeds fully. The overall reaction conditions are: stirring at 50℃ for 6 hours. After the reaction is complete, cool the solution to room temperature, then dialyze it with Milli-Q water for 1 week. Finally, freeze-dry the dialyzed solution to obtain methacrylated fucoidan (F-MA).

[0043] Weigh 1g of gelatin powder and add it to 10mL of PBS. Stir at 50℃ until completely dissolved. Then, add methacrylic anhydride (MA) dropwise under continuous stirring and react in the dark for 4 hours. After the reaction is complete, dilute with 5 times the volume of PBS to terminate the reaction. Then place the solution in a dialysis bag with a molecular weight cutoff of 8000Da~12000Da and dialyze with Milli-Q water for 1 week. Finally, obtain methacrylamide gelatin (Gel MA) by freeze drying.

[0044] Preparation of composite hydrogels with controlled release of carbon dots (F-MA / Gel MA CH composite hydrogel): F-MA and Gel MA were prepared into aqueous solutions with a mass-volume concentration of 3% (w / v) and 5% (w / v), respectively. The two solutions were mixed evenly at a volume ratio of 1:1 to obtain a hydrogel substrate prepolymer solution. CAC4A·His CDs complex was added to the hydrogel substrate prepolymer solution to make its concentration in the final system 500 μg / mL, and stirred to disperse evenly. Then, photoinitiator LAP was added at an amount of 0.25% (w / w) of the total mass of the hydrogel substrate prepolymer solution, and stirred until completely dissolved to obtain a mixed solution. Finally, the mixed solution was irradiated under 405 nm wavelength blue light for 5 min to form a composite hydrogel with carbon dots loaded and released in a controlled manner, namely F-MA / Gel MA CH composite hydrogel.

[0045] Example 2 A method for preparing a composite hydrogel loaded with carbon dots and capable of controlled release includes the following steps: Preparation of CAC4A·His CDs complex: S1. Weigh 1g of histidine (His) and add it to 20mL of deionized water. Stir until completely dissolved to obtain a clear His solution with a concentration of 50mg / mL, which is used as the reaction precursor. Transfer the His clear solution to a high-pressure reactor with a polytetrafluoroethylene liner and react at 180℃ for 6h. After the reaction is completed, allow it to cool naturally to room temperature. Filter the resulting reaction solution to remove large particulate impurities, and then dialyze it in a dialysis bag with a molecular weight cutoff of 1000Da for 24h. Finally, freeze-dry to obtain histidine carbon quantum dot (His CDs) powder.

[0046] S2. Weigh 4-aminobenzoic acid (10 mmol) and dissolve it together with concentrated hydrochloric acid (2 mL) in 15 mL of deionized water. Cool it to 0 °C in an ice-water bath, and then slowly add sodium nitrite aqueous solution (10 mmol) under stirring. Stir for 1 h to obtain a diazonium salt solution. Weigh 25,26,27,28-tetrahydroxycalix[4]arene (C4A, 2.36 mmol) and sodium acetate (30 mmol), dissolve them in 26 mL of methanol-N,N-dimethylformamide mixed solvent (methanol to DMF volume ratio of 5:8), and stir until dissolved to obtain C 4A solution, and then at 5℃ and under stirring conditions, the diazonium salt solution was slowly added dropwise to the C4A solution. After the addition was completed, the reaction continued at the same temperature for 2.5h. After the reaction was completed, the pH of the solution was adjusted to 0.9 with hydrochloric acid, and then the temperature was raised to 50℃ and the reaction was carried out for 45min. After the reaction was completed, the reaction system was cooled to room temperature, and the resulting suspension was centrifuged at 8000rpm for 10min and the precipitate was collected. The precipitate was washed with deionized water and anhydrous ethanol in sequence, and finally dried in a vacuum drying oven at 40℃ to obtain the brick red solid product carboxylated azocalix[4] aromatic hydrocarbon (CAC4A).

[0047] S3. Prepare an aqueous solution of His CDs powder with a concentration of 2000 μg / mL as His CDs stock solution. Under stirring conditions, add CAC4A solution to the His CDs stock solution to make the final concentration of His CDs in the mixture 1000 μg / mL and the final concentration of CAC4A 500 μg / mL. Then stir in the dark for 10 min and obtain the CAC4A·His CDs complex through self-assembly by host-guest interaction.

[0048] Preparation of F-MA and Gel MA: Weigh 1g of fucoidan and add it to 100mL of deionized water. Heat the solution to 60℃ and stir continuously to fully dissolve the fucoidan, preparing a solution with a concentration of 10mg / mL. While stirring, slowly add 12mL of methacrylic anhydride (MA) to the solution. Continue stirring for 30min, then adjust the pH of the system to 9.0 with sodium hydroxide. Continue the reaction for 5h, then adjust the pH to 9.0 again to ensure the reaction is complete. The overall reaction conditions are: stirring at 60℃ for 6h. After the reaction is complete, cool the solution to room temperature, then dialyze it with Milli-Q water for 1 week. Finally, freeze-dry the dialyzed solution to obtain methacrylated fucoidan (F-MA).

[0049] Weigh 1g of gelatin powder and add it to 10mL of PBS. Stir at 50℃ until completely dissolved. Then, add methacrylic anhydride (MA) dropwise under continuous stirring and react in the dark for 5h. After the reaction is complete, dilute with 5 times the volume of PBS to terminate the reaction. Then place the solution in a dialysis bag with a molecular weight cutoff of 8000Da~12000Da and dialyze with Milli-Q water for 1 week. Finally, obtain methacrylamide gelatin (Gel MA) by freeze drying.

[0050] Preparation of composite hydrogels with controlled release of carbon dots (F-MA / Gel MA CH composite hydrogel): F-MA and Gel MA were prepared into aqueous solutions with a mass-volume concentration of 4% (w / v) and 10% (w / v), respectively. The two solutions were mixed evenly at a volume ratio of 1:1 to obtain a hydrogel substrate prepolymer solution. CAC4A·His CDs complex was added to the hydrogel substrate prepolymer solution to make its concentration in the final system 400 μg / mL, and stirred to disperse evenly. Then, photoinitiator LAP was added at an amount of 0.25% (w / w) of the total mass of the hydrogel substrate prepolymer solution, and stirred until completely dissolved to obtain a mixed solution. Finally, the mixed solution was irradiated under 405 nm blue light for 3 min to form a composite hydrogel with carbon dots loaded and released in a controlled manner, namely F-MA / Gel MA CH composite hydrogel.

[0051] Example 3 A method for preparing a composite hydrogel loaded with carbon dots and capable of controlled release includes the following steps: Preparation of CAC4A·His CDs complex: S1. Weigh 1g of histidine (His) and add it to 20mL of deionized water. Stir until completely dissolved to obtain a clear His solution with a concentration of 50mg / mL, which is used as the reaction precursor. Transfer the His clear solution to a high-pressure reactor lined with polytetrafluoroethylene and react at 180℃ for 8h. After the reaction is completed, allow it to cool naturally to room temperature. Filter the resulting reaction solution to remove large particulate impurities, and then dialyze it in a dialysis bag with a molecular weight cutoff of 1000Da for 24h. Finally, freeze-dry to obtain histidine carbon quantum dots (His CDs) powder.

[0052] S2. Weigh 4-aminobenzoic acid (10 mmol) and dissolve it together with concentrated hydrochloric acid (2 mL) in 15 mL of deionized water. Cool it to 3 °C in an ice-water bath, and then slowly add sodium nitrite aqueous solution (10 mmol) under stirring. Stir for 45 min to obtain a diazonium salt solution. Weigh 25,26,27,28-tetrahydroxycalix[4] aromatic hydrocarbon (C4A, 2.36 mmol) and sodium acetate (30 mmol), dissolve them in 26 mL of methanol-N,N-dimethylformamide mixed solvent (methanol to DMF volume ratio of 5:8), and stir until dissolved. C4A solution was obtained, and then the diazonium salt solution was slowly added dropwise to the C4A solution at 5℃ and under stirring conditions. After the addition was completed, the reaction was continued at the same temperature for 3h. After the reaction was completed, the pH of the solution was adjusted to 1.2 with hydrochloric acid, and then the temperature was raised to 55℃ and the reaction was carried out for 15min. After the reaction was completed, the reaction system was cooled to room temperature, and the resulting suspension was centrifuged at 8000rpm for 10min and the precipitate was collected. The precipitate was washed with deionized water and anhydrous ethanol in sequence, and finally dried in a vacuum drying oven at 40℃ to obtain the brick-red solid product carboxylated azocalix[4] aromatic hydrocarbon (CAC4A).

[0053] S3. Prepare an aqueous solution of His CDs powder with a concentration of 2000 μg / mL as His CDs stock solution. Under stirring conditions, add CAC4A solution to the His CDs stock solution to make the final concentration of His CDs in the mixture 1000 μg / mL and the final concentration of CAC4A 500 μg / mL. Then stir in the dark for 1 h to obtain the CAC4A·His CDs complex through self-assembly by host-guest interaction.

[0054] Preparation of F-MA and Gel MA: Weigh 1g of fucoidan and add it to 100mL of deionized water. Heat the solution to 40℃ and stir continuously to fully dissolve the fucoidan, preparing a solution with a concentration of 10mg / mL. While stirring, slowly add 12mL of methacrylic anhydride (MA) to the solution. Continue stirring for 2 hours, then adjust the pH of the system to 8.5 with sodium hydroxide. Continue the reaction for 3 hours, then adjust the pH to 8.5 again to ensure the reaction proceeds fully. The overall reaction conditions are: stirring at 40℃ for 6 hours. After the reaction is complete, cool the solution to room temperature, then dialyze it with Milli-Q water for 1 week. Finally, freeze-dry the dialyzed solution to obtain methacrylated fucoidan (F-MA).

[0055] Weigh 1g of gelatin powder and add it to 10mL of PBS. Stir at 50℃ until completely dissolved. Then, add methacrylic anhydride (MA) dropwise under continuous stirring and react in the dark for 6 hours. After the reaction is complete, dilute with 5 times the volume of PBS to terminate the reaction. Then place the solution in a dialysis bag with a molecular weight cutoff of 8000Da~12000Da and dialyze with Milli-Q water for 1 week. Finally, obtain methacrylamide gelatin (Gel MA) by freeze drying.

[0056] Preparation of composite hydrogels with controlled release of carbon dots (F-MA / Gel MA CH composite hydrogel): F-MA and Gel MA were prepared into aqueous solutions with a mass-volume concentration of 2% (w / v) and 6% (w / v), respectively. The two solutions were mixed evenly at a volume ratio of 1:1 to obtain a hydrogel substrate prepolymer solution. CAC4A·His CDs complex was added to the hydrogel substrate prepolymer solution to make its concentration in the final system 300 μg / mL, and stirred to disperse evenly. Then, photoinitiator LAP was added at an amount of 0.25% (w / w) of the total mass of the hydrogel substrate prepolymer solution, and stirred until completely dissolved to obtain a mixed solution. Finally, the mixed solution was irradiated under 405 nm blue light for 1 min to form a composite hydrogel with carbon dots loaded and released in a controlled manner, namely F-MA / Gel MA CH composite hydrogel.

[0057] Performance evaluation: Examples 1 to 3 of this invention all yielded composite hydrogels with controlled release of carbon dots that exhibit excellent repair capabilities for infected bone defects. The F-MA / Gel MA CH composite hydrogel from Example 1 is used as an example for further research. Specific research methods and results are shown below: Figure 1The image shows a TEM image (scale bar: 20 nm) of His CDs from Example 1. As shown, the synthesized His CDs exhibit a uniform spherical morphology and good dispersibility with no obvious agglomeration, indicating that the method of the present invention successfully obtained histidine carbon quantum dots with excellent monodispersity.

[0058] Figure 2 The hypoxia-responsive release behavior of CAC4A·His CDs in Example 1 was recorded. To verify the responsiveness of CAC4A·His CDs, sodium dithionite (SDT) at a final concentration of 10 mM was introduced into the experimental system to simulate a hypoxic microenvironment in vitro. The results showed that His CDs alone exhibited fluorescence properties, emitting strong fluorescence under 360 nm excitation light; when bound to CAC4A, the fluorescence was strongly quenched at 457 nm. Crucially, after adding SDT to simulate hypoxic conditions, His CDs could be effectively released from CAC4A·His CDs, accompanied by a significant recovery of the fluorescence signal, thus confirming its hypoxia-responsive release characteristics.

[0059] Figure 3 The results of the in vitro antibacterial performance test of His CDs in Example 1 are shown. This test was conducted using Staphylococcus aureus (S. aureus) as the target bacteria. S.aureus ) and Escherichia coli ( E. coli These two bacteria were used as representative Gram-positive and Gram-negative bacteria, respectively. After being cultured overnight in liquid medium, both bacteria were diluted to 1×10⁻⁶ with sterile PBS. 5 CFU / mL. 1 mL of bacterial suspension was co-cultured with His CDs solution (final concentration 1 mg / mL) for 1 h, during which time it was irradiated with a xenon lamp (PL-XQ500W) for 5 min. This group was designated "Example 1 + Light Group". Bacterial suspension without His CDs was used as a control. After treatment, 50 μL of bacterial suspension from each group was evenly spread on the surface of a solid culture medium and incubated at 37℃ for 24 h. Finally, the colonies on the plates were photographed and recorded. The experimental results showed that compared with the control group without His CDs treatment, the number of colonies formed in Example 1 + Light Group was significantly reduced, indicating its effectiveness in treating His CDs. S.aureus and E. coli The antibacterial rates reached 96.81% and 93.85%, respectively. This result confirms that the HisCDs prepared in this invention can produce significant antibacterial effects under light irradiation.

[0060] Figure 4This is a schematic diagram illustrating the formation process of the composite hydrogel with controlled release of carbon dots in Example 1. The composite hydrogel with controlled release of carbon dots consists of the following components: a milky white F-MA solution and a Gel MA solution, and brick-red CAC4A powder loaded with HisCDs. After cross-linking via photo-initiated free radical polymerization, a red three-dimensional network gel structure is formed.

[0061] Figure 5 The image shows the SEM morphology of the carbon dot-loaded and controllably released composite hydrogel of Example 1 at a magnification of 1KX. As shown in the figure, the carbon dot-loaded and controllably released composite hydrogel of the present invention exhibits a porous network structure with excellent uniformity, specifically characterized by uniform pore size and highly ordered spatial arrangement.

[0062] Figure 6 This image shows the results of the composite hydrogel loaded with carbon dots and controlled release, as described in Example 1, promoting osteogenic differentiation of BMSCs in vitro. Specifically, BMSCs were loaded with 5 × 10⁻⁶ carbon dots and controlled release. 4 Cells were seeded at a density of 1:1 / well in 24-well plates and co-cultured with a carbon-dot-loaded, controllably released composite hydrogel for 7 days. ALP staining was performed using an ALP staining kit: cells were fixed with 4% paraformaldehyde, reacted with working solution for 30 min, washed with PBS, and the ALP staining results were observed under an optical microscope. It was observed that the carbon-dot-loaded, controllably released composite hydrogel group of Example 1 showed significantly enhanced ALP activity compared to the control group (manifested as a larger area of ​​blue-purple staining). These results indicate that the carbon-dot-loaded, controllably released composite hydrogel of the present invention has good osteogenic induction activity.

[0063] Figure 7 This is a schematic diagram illustrating how the carbon-dot-loaded, controllably released composite hydrogel promoted the repair of infected skull bones in vivo, as described in Example 1. Rats were anesthetized with sodium pentobarbital and fixed on a sterile operating table. Hair was removed from the skull area, and after disinfection, subcutaneous tissue and muscle were dissected layer by layer using sterile scissors to fully expose the skull surface. After peeling off the periosteum, a circular defect model with a diameter of 3 mm was created at the top of the skull using a high-speed dental drill. Eight weeks post-surgery, the rats were sacrificed, and skull samples were collected. Three-dimensional imaging and bone regeneration analysis of the samples were performed using a micro-CT scanner. The results showed that, compared with the control group, the experimental group implanted with the carbon-dot-loaded, controllably released composite hydrogel had a significantly smaller skull defect area, and newly formed bone tissue essentially covered the defect area. This indicates that the carbon-dot-loaded, controllably released composite hydrogel of this invention can effectively promote bone defect repair under infected conditions.

[0064] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, it is intended to include any modifications and variations of this invention that fall within the scope of the claims and their equivalents.

Claims

1. A composite hydrogel loaded with carbon dots and capable of controlled release, characterized in that, A composite hydrogel loaded with carbon dots and capable of controlled release serves as a carbon dot control unit encapsulated in a hydrogel matrix. The carbon dot control unit is a CAC4A·His CDs complex, which is prepared according to the following steps: Histidine carbon quantum dots, or His CDs, are obtained by hydrothermal reaction of histidine aqueous solution. 4-Aminobenzoic acid and concentrated hydrochloric acid were dissolved together in water, and sodium nitrite was added dropwise under ice-water bath conditions to carry out a diazotization reaction to obtain a diazonium salt solution; 25,26,27,28-tetrahydroxycalix[4]arene and sodium acetate were dissolved together in a solvent to obtain a C4A solution; the diazonium salt solution was added dropwise to the C4A solution and an electrophilic substitution reaction was carried out to obtain carboxylated azocalix[4]arene, namely CAC4A; CAC4A was used as the host and His CDs was used as the guest, and they were mixed in water and then stirred in the dark. The host and guest were combined through non-covalent bonds, so that the two were self-assembled to obtain the CAC4A·His CDs complex; The hydrogel matrix consists of methacrylated gelatin and methacrylated fucoidan; the methacrylated fucoidan is prepared by the following steps: an aqueous solution of fucoidan is mixed with methacrylic anhydride and then subjected to an esterification reaction to obtain methacrylated fucoidan, i.e., F-MA; the methacrylated gelatin is prepared by the following steps: a gelatin solution is mixed with methacrylic anhydride and then subjected to an amidation reaction to obtain methacrylated gelatin, i.e., Gel MA; The encapsulation method is as follows: F-MA aqueous solution and Gel MA aqueous solution are mixed to obtain hydrogel substrate prepolymer solution. CAC4A·His CDs complex and photoinitiator are mixed into hydrogel substrate prepolymer solution. F-MA and Gel MA encapsulate CAC4A·His CDs complex. Photoinitiated free radical polymerization crosslinking reaction is carried out under blue light. F-MA and Gel MA form a three-dimensional network structure through photoinitiated free radical polymerization crosslinking to obtain composite hydrogel with carbon dots loaded and controllable release.

2. The composite hydrogel with loaded carbon dots and controllable release according to claim 1, characterized in that, The hydrothermal reaction conditions are: reacting at 180℃ for 6 to 10 hours.

3. The composite hydrogel with loaded carbon dots and controllable release according to claim 1, characterized in that, The mass ratio of 4-aminobenzoic acid to 25,26,27,28-tetrahydroxycalix[4] aromatic hydrocarbon is 1~3:0.5~2.

4. The composite hydrogel with loaded carbon dots and controllable release according to claim 1, characterized in that, During self-assembly, stirring should be performed in the dark for 10 minutes to 1 hour.

5. The composite hydrogel with loaded carbon dots and controllable release according to claim 1, characterized in that, His CDs have a mass ratio of 10~20:3~5 to CAC4A.

6. The composite hydrogel with loaded carbon dots and controllable release according to claim 1, characterized in that, The mass ratio of fucoidan to methacrylic anhydride is 1~3:4~12.

7. The composite hydrogel with loaded carbon dots and controllable release according to claim 1, characterized in that, The mass ratio of gelatin to methacrylic anhydride is 0.5~2:1~4.

8. The composite hydrogel with loaded carbon dots and controllable release according to claim 1, characterized in that, In the hydrogel substrate prepolymer solution, the mass-volume concentration of F-MA is 2%~4%, the mass-volume concentration of Gel MA is 5%~10%, and the mass concentration of CAC4A·HisCDs composite is 300μg / mL~500μg / mL.

9. The composite hydrogel with loaded carbon dots and controllable release according to claim 1, characterized in that, The conditions for photo-initiated free radical polymerization crosslinking reaction are: irradiation with 405nm blue light for 1-5 minutes.

10. The application of the composite hydrogel with loaded carbon dots and controllable release as described in claim 1 in the preparation of materials for repairing infected bone defects.

Citation Information

Patent Citations

  • Azo calixarene pharmaceutic adjuvant and application thereof

    CN114848839A

  • Preparation method and application of green luminous amino acid derived antibacterial carbon dots

    CN117431062A